Themes-based classification for Al-Quran knowledge ontology - Ta'a, Azman; Abdullah, Mohd Syazwan; Mat Ali, Abdul Bashah; Ahmad, Muhammad (2014)
Al-Quran knowledge representations involved classification of Al-Quran verses for providing better understanding of the readers. In the current era of social media challenges. the representation of knowledge must be understood by human and computer in order to ensure the correctness of Al-Quran semantics are persevered.Current approaches used conventional methods such as taxonomy, hierarchy or tree structure, which only provides a concept definition without linked to other sources of knowledge explanation. This research aims to develop the Al-Quran Ontology by using theme-based classification approach.The ontology model for Al-Quran is developed based on the Al-Quran knowledge theme defined in Syammil Al-Quran Miracle the Reference.The theme-based ontology approach has shown that the Al-Quran knowledge can be classified and presented systematically.This will encourage the development of applications for Al-Quran readers.Moreover, the ontology structure that representing the theme concepts in Al-Quran was reviewed and validated by the domain experts in Al-Quran knowledge.